Stock assessment of Metapenaeus monoceros (Fabricius) from Cochin waters, Kerala - Nandakumar, G; Srinath, M (Indian Journal of Fisheries, 2011)
Based on the catch and effort, and length distribution data of Metapenaeus monoceros landed by shrimp trawlers at Cochin Fisheries Harbour during 1991 - 93, an attempt has been made to assess the stock of this species in the Cochin waters. The average annual instantaneous rate of total mortality was estimated 7.06 and 7.75 for females and males respectively. The estimated value of annual natural mortality (M) was 2.35 and it was assumed to be the same for both sexes. The estimate of fishing mortality rate (F) was 4.71 for females and 5.40 for males of M. monoceros. The average rate of exploitation (E) was 0.70 and 0.67 respectively for males and females. The average standing stock size of M. monoceros for the period under study was 10.55 t for males and 28.65 t for females. The Thomson and Bell and the Beverton and Holt yield per recruit routines in the LFSA are used to explain the present status of fishery which shows that there is no adverse effect of fishing on the exploited stock of M. monoceros from the southwest coast off Cochin.